2010
DOI: 10.1007/s11259-009-9339-8
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in bovine CD14 positive cells in colostrum is associated with the incidence of mastitis after calving

Abstract: During the postpartum period there is a high incidence of mastitis in dairy cows. The reason for this increased risk of mastitis still remains unclear. Since leukocytes in colostrum have an important role in preventing the onset of mastitis, we investigated the leukocyte populations, which express CD4, CD8, CD14, CD21 or WC1, in colostrum as well as in blood obtained from 14 Holstein cows. Eight cows developed mastitis within a week after calving and the other 6 remained healthy. The percentage of CD14+ cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
4
6
0
Order By: Relevance
“…In the present study, the mean percentages of CD2 + and CD14 + CMC were comparable or lower than percentages found in previous studies (Park et al, 1992;Yang et al, 1997;Kiku et al, 2010). The mean percentage of CD21 + CMC was much lower than the percentage of B-lymphocytes found in bovine colostrum in other studies (Park et al, 1992;Kiku et al, 2010). Our results concerning B-lymphocytes agree with others (Taylor et al, 1994;Harp et al, 2004), as T-lymphocytes traffic selectively into bovine mammary gland secretions whereas B-lymphocytes represent a minor population as compared with peripheral blood.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In the present study, the mean percentages of CD2 + and CD14 + CMC were comparable or lower than percentages found in previous studies (Park et al, 1992;Yang et al, 1997;Kiku et al, 2010). The mean percentage of CD21 + CMC was much lower than the percentage of B-lymphocytes found in bovine colostrum in other studies (Park et al, 1992;Kiku et al, 2010). Our results concerning B-lymphocytes agree with others (Taylor et al, 1994;Harp et al, 2004), as T-lymphocytes traffic selectively into bovine mammary gland secretions whereas B-lymphocytes represent a minor population as compared with peripheral blood.…”
Section: Discussionsupporting
confidence: 83%
“…Cows in parity ≥4 suffered from more profound periparturient impairment of neutrophil function than younger cows (Gilbert et al, 1993), again confirming the present results. In the present study, the mean percentages of CD2 + and CD14 + CMC were comparable or lower than percentages found in previous studies (Park et al, 1992;Yang et al, 1997;Kiku et al, 2010). The mean percentage of CD21 + CMC was much lower than the percentage of B-lymphocytes found in bovine colostrum in other studies (Park et al, 1992;Kiku et al, 2010).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…+ proportion of about 60% in the peripheral blood of lactating dairy cows and Kiku et al (2010) who reported a rate of about 40% in cows postpartum.…”
Section: Discussionmentioning
confidence: 94%
“…The gene function of CD14 and several inflammatory cytokines has been widely explored in certain diseases that are caused by Gram-negative bacteria in humans, mice and livestock. Examples include endometritis, Brucella and mastitis [12][13][14]. Most of our understanding of the molecular regulatory mechanism of CD14 has been based on the results of mouse RAW264.7 macrophage studies [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%